2020
DOI: 10.24042/tadris.v5i2.6388
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of Students' Scientific Argumentation Skills Test in Acid-Base Chemistry

Abstract: This study aimed to develop and validate Scientific Argumentation Skills Test (SAST) and investigate the 11th-grade students' performance in scientific argumentation skills on acid-base chemistry. The research design used was research and development, followed by descriptive research. Research and development were carried out to obtain an instrument of SAST, and descriptive research was used to describe students' argumentation skills in acid-base chemistry. Participants in this study were 328 11th-grade studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…At the first level, students can only submit a claim without providing evidence and reasons to support the claim that has been stated in the answer choices. To make a claim, students do not need to think critically, but students only need to recognize, remember, understand, classify, and apply their knowledge (Parlan et al, 2020). The second level of argumentation already provides evidence and reasons to support a claim but does not provide a rebuttal.…”
Section: Results and Diccussion Resultsmentioning
confidence: 99%
“…At the first level, students can only submit a claim without providing evidence and reasons to support the claim that has been stated in the answer choices. To make a claim, students do not need to think critically, but students only need to recognize, remember, understand, classify, and apply their knowledge (Parlan et al, 2020). The second level of argumentation already provides evidence and reasons to support a claim but does not provide a rebuttal.…”
Section: Results and Diccussion Resultsmentioning
confidence: 99%
“…However, according to Lam et al (2018), the major challenge students may probably face in their argumentative writing is their ability to organize and formulate their arguments. For instance, most students find it challenging to explain why a piece of evidence can support a particular claim (Parlan et al, 2020; Walker et al, 2019). Lammers et al (2019) also found that most students find it challenging to understand the rhetorical meaning of qualifiers, and hence, they do not use a qualifier in their conclusion of an argument.…”
Section: Argumentationmentioning
confidence: 99%
“…Namun, sedikit literatur yang tersedia tentang studi pengembangan tes argumentasi ilmiah dan survei ketrampilan argumentasi siswa terutama pada kimia. Instrumen dalam kimia saat ini ada untuk kesetimbangan kimia, asam basa, dan hidrolisis garam Parlan et al, 2020). Belum ada penelitian untuk mengembangkan instrumen argumentasi tentang laju reaksi dan menyelidiki kemampuan argumentasi siswa pada topik tersebut.. Untuk itu, penelitian ini bertujuan untuk mengembangkan tes argumentasi ilmiah yang valid dan reliabel pada laju reaksi dan menginvestigasi keterampilan argumentasi ilmiah siswa.…”
Section: Pendahuluanunclassified
“…Hasil juga menunjukkan bahwa siswa belum terampil dalam menjelaskan mengapa bukti dapat mendukung klaim. Temuan ini sejalan dengan penelitian Sadler (2004), Sampson & Clark (2009), dan Parlan et al (2020). Ketika mereka memberikan bukti yang tidak tepat, maka penjelasan yang dibangun tidak berkesinambungan dengan klaim yang dinyatakan.…”
Section: Bukti Yang Benar (Diperoleh Dari Observasi Data)unclassified